Use of animation in classrooms at higher learning institutions: student perception / Nalini Arumugam … [et al.] - Arumugam, Nalini; Suppiah, Puspalata C; Supramaniam, Kaarthiyainy; Manap, Mohammad Radzi (Akademi Pengajian Bahasa, 2021)
The integration of animation in classroom learning among students at higher learning institutions has become one of the most important and reliable instruments. With more emphasis placed on quality education, the use of modern instructional materials is paramount. This study aims to identify the students' perceptions towards animation in their learning environment specifically in higher learning institutions in Malaysia. An online survey using Google form application was distributed to 275 undergraduates. Data elicited from the respondents were analysed using quantitative research approach. The findings indicated that majority of the undergraduates have shown interest in the use of animation in their classroom teaching and learning activities due to its effectiveness in facilitating learning. They found animations to be an efficient way to deliver and disseminate information, thus making their learning more stimulating besides enhancing their knowledge in computer skills. The respondents further indicated that animation not only helped them to understand a complex concept easily but also made their presentations more appealing. Conversely, it was also noted that to create even the simplest animation, a lot of time and effort is needed. Besides, too much animation on the page can be distracting. This study concludes with an overall discussion and recommendations for further study.